2020
DOI: 10.1159/000507918
|View full text |Cite
|
Sign up to set email alerts
|

High White Blood Cell Count Is a Risk Factor for Contrast-Induced Nephropathy following Mechanical Thrombectomy for Acute Ischemic Stroke

Abstract: Background: Although mechanical thrombectomy is a standard endovascular therapy for patients with acute ischemic stroke (AIS), the incidence of and risk factors for contrast-induced nephropathy (CIN) following mechanical thrombectomy are infrequently reported. Objectives: The aim of this study was to investigate the incidence and risk factors for CIN following mechanical thrombectomy for AIS, and whether the incidence of CIN is related to a poor prognosis. Methods: We examined consecutive patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Yamamoto et al found, through multivariate analysis, that high preoperative WBC count was a novel risk factor for developing CIN following mechanical thrombectomyan. 33 Similar reports show an increase in inflammation-related molecules in CIN after PCI, including WBC counts (especially neutrophils). 34 Inflammatory cells cause the release of oxygen free radicals, vasoconstrictors, leukotrienes and thromboxane, leading to kidney damage.…”
Section: Discussionmentioning
confidence: 63%
“…Yamamoto et al found, through multivariate analysis, that high preoperative WBC count was a novel risk factor for developing CIN following mechanical thrombectomyan. 33 Similar reports show an increase in inflammation-related molecules in CIN after PCI, including WBC counts (especially neutrophils). 34 Inflammatory cells cause the release of oxygen free radicals, vasoconstrictors, leukotrienes and thromboxane, leading to kidney damage.…”
Section: Discussionmentioning
confidence: 63%
“…Yoo et al ., in a study of 601 MT-treated patients, concluded that factors independently associated with AKI were diabetes, total contrast dose and unsuccessful reperfusion [ 12 ]. In a study by Yamamoto et al ., including 80 patients after MT, contrast-induced nephropathy was independently predicted by white blood cell count and the quotient of contrast volume and estimated glomerular filtration rate [ 17 ]. In a study by Weber et al among 1017 MT-treated AIS patients those who developed AKI compared to those without AKI significantly more often suffered from diabetes and chronic kidney disease and more frequently had a tandem occlusion, but multivariate logistic regression analysis revealed no significant independent risk factors for AKI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inflammation may play an important role in the initiation and extension phases of CA-AKI. Inflammatory cells infiltrate the interstitium of the kidney via cytokines produced by renal endothelial cells, and cause the release of oxygen radicals, vasoconstrictors, and thromboxanes, leading to kidney damage [ 24 , 25 ]. STEMI patients had increased systemic inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%